Power-take-off from Single-phase-to-earth Fault Current to Power Supply Identification Devices - Bezruchko, V. M.; Buinyi, R. O.; Tkach, V. I. (Visnyk of Vinnytsia Politechnical Institute, 2020)
In Ukraine, 6–35 kV electric networks operate in isolated neutral mode, which allows the networks to remain operational when single-phase-to-earth fault takes place. However, the presence of such a fault increases the possibility of interphase fault. Therefore, these faults are to be eliminated as quickly as possible. Existing devices can only narrow the search area to the detected branch from the overhead line, then an emergency crew has to find the fault by going along the line and inspecting it visually. The authors proposed an innovative device for identifying the single-phase-to-earth fault, which allows to determine the location of a fault with accuracy to the overhead line support, provided that such devices are available on each support. Such a device, having identified the presence of a single-phase-to-earth fault on the support, sends a message through the GSM network to the control center. The paper analyzes the possible power sources of such a device. It is proposed to power the device directly from the fault current. It is proposed to perform power take-off from the current through the metal grounding of the support using a special transformer that will maximize power take-off and maintain the integrity of the support ground loop. There has been proposed a mathematical model, which allows to calculate the parameters of the operating mode of such a transformer at various values of the fault currents and its dimension. It is shown that the proposed approach to the construction of a power source allows selecting enough energy that can be accumulated in capacitive storage and used to power the device while sending a message about the place of fault on the overhead line. It is shown that the maximum time of energy storage and sending messages can reach 10 minutes. During this time, the emergency crew should prepare for departure to search for the fault.